Utilization of BCFS (Biomass Coal Fuel-Sludge) As Substitution of Energy Sources in Industrial Boilers: Pemanfaatan BCFS (Biomass Coal Fuel-Sludge Sebagai Substitusi Sumber Energi di Boiler Industri - Arifin, Danang Nor; Hidawati, Hidawati (Procedia of Engineering and Life Science, 2023)
The utilization of coal as an energy source is still the main choice of the textile industry in Indonesia. The process of this utilization left 20% of FABA (fly ash-bottom ash) where 80% of them were bottom ashes which are considered hazardous and toxic waste. This study aims to obtain the technology and production process for treating bottom ash and biomass from urban waste as an alternative energy source and reducing environmental problems (zero waste: waste to energy and waste to material). Biomass Coal Fuel-Sludge (BCFS) Briquettes as a product derived from bottom ash, biomass, and biosludge had a composition of 50%: 30%: 20%. The briquettes utilization can reduce coal use by 16% and increase boiler temperature to 35°C - 75°C. The emission in the trial burning test which were the particulates, sulfur dioxide, and nitrogen dioxide met the quality standards required in the Technical Approval in the Sector of Hazardous Waste Management from the Ministry of Environment and Forestry. With this research, the BCFS briquette products can be a solution to the utilization of B3 waste and waste problems.